2016
DOI: 10.3389/fpls.2016.00164
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Soil Suppressiveness to Root-Knot Nematodes in Organic Horticulture in Plastic Greenhouse

Abstract: The fluctuation of Meloidogyne population density and the percentage of fungal egg parasitism were determined from July 2011 to July 2013 in two commercial organic vegetable production sites (M10.23 and M10.55) in plastic greenhouses, located in northeastern Spain, in order to know the level of soil suppressiveness. Fungal parasites were identified by molecular methods. In parallel, pot tests characterized the level of soil suppressiveness and the fungal species growing from the eggs. In addition, the egg para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 52 publications
4
54
0
Order By: Relevance
“…Dasher II was grafted onto Cucurbita maxima x C. moschata hybrid RS841 by tongue approach, because it is easy to apply, successful, and provides a uniform growth rate (Davis et al 2008 ). The squash hybrid RS841 has been proven to develop a longer root system than cucumber and to improve crop yield (Maršić and Jakše 2010 (Giné et al 2016 ). Plants were irrigated as needed through a drip irrigation system and weekly fertilized with a solution consisting of NPK (15-5-30) at 31 kg ha and iron chelate and micronutrients at 0.9 kg ha .…”
Section: Introductionmentioning
confidence: 99%
“…Dasher II was grafted onto Cucurbita maxima x C. moschata hybrid RS841 by tongue approach, because it is easy to apply, successful, and provides a uniform growth rate (Davis et al 2008 ). The squash hybrid RS841 has been proven to develop a longer root system than cucumber and to improve crop yield (Maršić and Jakše 2010 (Giné et al 2016 ). Plants were irrigated as needed through a drip irrigation system and weekly fertilized with a solution consisting of NPK (15-5-30) at 31 kg ha and iron chelate and micronutrients at 0.9 kg ha .…”
Section: Introductionmentioning
confidence: 99%
“…Root-knot nematodes are common and destructive plant parasitic nematodes which have wide host range and can significant yield loss in many crops (Giné et al 2016). They are polyphagous and reported in many crops such as tomato, brinjal, okra, potato, chilly, radish, carrot, onion, cabbage, cauliflower, lettuce, chickpea, broad bean, cowpea, cucumber, pumpkin and various gourds from plains to high hills of the country Shrestha 1969, PPD 2009).…”
Section: Discussionmentioning
confidence: 99%
“…In tomato, root-knot nematodes are major biotic factor which is responsible for low yield (Giné et al 2016). It has been reported that on an average of 30 percent tomato fruits was reduced due to the nematodes in plastic tunnels at Hemja of Kaski district (PPD 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The site M10.55 was a sandy clay loam soil (68% sand, 0% silt, and 32% clay), pH 8.1, 2.5 organic matter (w/w), and 1,069 µS cm −1 electric conductivity. Both soils were previously characterized as suppressive to Meloidogyne, with P. chlamydosporia as the only fungal species recovered from RKN-parasitized eggs (Giné et al, 2016). Each soil was mixed with steam-sterilized sand at a ratio of 1:1 (dry w/dry w), to avoid soil compaction and to improve plant growth, and served as substrate for cropping tomato plants in 3-l pots.…”
Section: Induction Of Systemic Plantmentioning
confidence: 99%
“…might limit growth of other soil microorganisms by predation or resource competition, including nematode antagonistic fungi such as Pochonia (Metacordyceps) chlamydosporia. This fungal species is frequently isolated from RKN eggs produced in vegetable crop roots cultivated in northeastern Spain (Giné et al, 2012) and has been reported as the main biotic factor responsible for soil suppressiveness to RKN in this area (Giné et al, 2016). In addition, it has been reported that some P. chlamydosporia strains can induce systemic resistance in tomato plants (Ghahremani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%